IDENTIFIKASI TINGKAT REAKTIFITAS KATALIS DASAR BESI JENIS LIMONIT DAN PIRIT PADA PROSES PENCAIRAN BATUBARA - Hanif, Muhammad; Hartiniati, Hartiniati (Badan Pengkajian dan Penerapan Teknologi, 2006)
The effect of a highly dispersed limonite synthetic catalyst and natural pyritecatalyst on the liquefaction of Yallourn coal in relation to thetransformation into pyrrhotite (Fe1-x S) was examined and compared. Thestudy suggests that ?-FeOOH catalyst can be transformed into smallerpyrrhotite at lower temperatures around 250oC, and therefore promotes theactivation of gaseous hydrogen notably at the heating stage up to 450oC.Keeping H2S concentration at approximately 0.1vol% in the gas phase wasfound to be an effective way of maintaining the liquefaction activity of therecycle catalyst, due to the restraint of both troilite formation and theagglomeration of pyrrhotite. The study also demonstrates that a high oilyield over 60wt% daf can be obtained successfully in the coal liquefaction ofYallourn coal with the reduction of catalyst ?-Fe00H loading.Kata Kunci : pyrrhotite, troilite, coal liquefaction, pyrite